Decomposition of HIV Knowledge In Urban-Rural Areas In Indonesia - Fadhaa Aditya Kautsar Murti; Asti Annisa Utami; Gastin Gabriel Jangkang (Jurnal Ilmu Kesehatan Masyarakat, 2024)
HIV/AIDS remains a public health crisis, HIV/AIDS remains a public health crisis, especially among male adolescents in Indonesia. This urgency stems from the rapid increase in cases among adolescents, who often lack adequate access to education and prevention resources. If left unaddressed, the epidemic could continue to spread among younger populations, leading to long-term social and economic consequences. Despite the crucial role of HIV knowledge in prevention, disparities exist between rural and urban areas. This study examines these disparities, identifying factors influencing HIV knowledge. This cross-sectional study employed a total of 10,943 male adolescents enrolled in a survey called Indonesia Demographic Health Survey (IDHS) 2017. To address those disparities, a stratification chi-square based on place of residence was employed. We also employed a multivariate decomposition analysis to examine which variables account for most gaps. Results found that only 15% of adolescents were knowledgeable (9.5% in urban and 5.5% in rural areas). Bivariate Analysis showed that education level and HIV test awareness were associated in both areas ( p-value < 0.05), while wealth quintile and internet use were associated in urban areas only ( p-values < 0.05). The HIV knowledge gap would decrease by 8% if internet use was equalized, by 11% if HIV testing awareness was equalized, by 17% if educational attainment was equalized, and by 24% if wealth quintiles were equalized. This calls for a multi-sectoral intervention targeting such factors for better HIV outcomes in Indonesia.